The Relationship Between the Implementation of 4C with Biology Learning Outcomes and Soft Skills of High School Students in Jayapura City - Rosaniya E. Rehiara; Paul J. Kawatu; Apriani H. Rophi; Ruth Megawati; David R. Jesajas (Postgraduate, University of Mataram, 2024)
This study highlights the 21st century global education policy, namely learning that emphasizes 4 important aspects, namely: Critical thinking, Communication, Collaboration, and Creativity, hereinafter abbreviated as 4 C. This study aims to determine the relationship between the application of four 21st century critical skills—critical thinking, communication, collaboration, and creativity (4C)—into biology learning and the impact or relationship to learning outcomes and Soft Skills of high school students in Jayapura City. The results showed that students in the “Sekolah Penggerak” had a higher level of mastery of the 4C and soft skills, such as adaptability, time management, empathy, ethical awareness, self-motivation, and initiative, compared to students in the “Regular School.” Although there was a significant correlation between 4C skills and soft skills, no substantial relationship was found between 4C skills and academic outcomes directly. This suggests that the learning approach applied in the “Sekolah Penggerak,” which is more interactive and collaborative, is more effective in supporting the development of soft skills than academic achievement. These findings highlight the importance of integrating 4C and soft skills development into the secondary education curriculum to prepare students for future challenges. Recommendations from this study encourage educators and policymakers to implement learning methods that support students' interpersonal skills and independence in all types of schools.